Analisis Wacana Kritis Novel Genduk Duku Karya Y.B Mangunwijaya dan Relevansinya dengan Pembelajaran Literasi Sastra berbasis Gender di SMA - Fatimah, Andi Anugrah Batari; Syamsudduha, Syamsudduha; Usman, Usman (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to analyze the novel Genduk Duku to find a position as a subject or object that experiences gender injustice and its relevance to gender-based literacy learning in high school. The research method used is a descriptive qualitative-critical linguistic method. The data techniques used were documentation, read, and record techniques. The data analysis technique used is the Sara Mills critical model analysis assisted by Mansour Fakih's theory of gender injustice with procedures, data reports, data classification, and data analysis. The results of the study found that the female characters in the novel, both the main character, Genduk Duku, and the supporting characters, Putri Arumardi and Tejarukmi, each took turns as actors who tell stories or who are told, all experience a form of gender, in terms of (a) marginalization, (b) subordination, (c) stereotyping, (d) verbal violence, (e) double burden in terms of women who work in the public sector and the domestic sector. This study can be integrated with gender-based literary literacy learning in high schools in terms of presenting a description of discourse that displays the practice of gender injustice and critical attitudes that students must take to change the practice of gender injustice.